2004
DOI: 10.1557/proc-841-r9.16
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Properties of ALD Coated MEMS

Abstract: A comparative study of the microtribological properties of native oxide covered single crystal silicon and silicon coated with atomic layer deposited (ALD) alumina films is presented. The dry friction and wear behavior were investigated using a novel microelectromechanical system (MEMS) tribotester. The coefficient of friction for alumina coated surfaces and for silicon uncoated surfaces was monitored before and after wear. The friction versus normal load curves of uncoated silicon can be described by a Johnso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Possible applications range from chemical and corrosion resistant coatings [19] to enhancement of mechanical properties of engineered parts. Examples of enhancements of mechanical properties, investigated for the MEMS applications, are solid lubricants [20] and tribological coatings [21]. High surface conformality of ALD enables reliable coating of complex parts as well, including inside of tubes [22] and cavities.…”
Section: Functional and Protective Coatingsmentioning
confidence: 99%
“…Possible applications range from chemical and corrosion resistant coatings [19] to enhancement of mechanical properties of engineered parts. Examples of enhancements of mechanical properties, investigated for the MEMS applications, are solid lubricants [20] and tribological coatings [21]. High surface conformality of ALD enables reliable coating of complex parts as well, including inside of tubes [22] and cavities.…”
Section: Functional and Protective Coatingsmentioning
confidence: 99%
“…In contrast to the other techniques tested, ALD allows highly conformal coatings to be deposited on high aspect ratio structures, which are typical of MEMS devices. 6 In fact, a recent report 7 has shown that the tribological characteristics of surfaces can be significantly improved through the use of ALD coatings, due to the highly uniform nature of the deposition. This is quantified with respect to the debris creation and the stability of the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] However, the main challenge is to package the MEMS devices to include the vapor feed system. Hard lms, such as diamond-like carbon (DLC), 14,15 tungsten (W), 16,17 silicon carbide (SiC), 18,19 titanium dioxide (TiO 2 ) 20,21 and alumina (Al 2 O 3 ) [22][23][24] can also reduce friction and wear of Si material, while how to coat the complicated structures of MEMS devices conformally is a matter of concern.…”
Section: Introductionmentioning
confidence: 99%